Increasing Soybean (Glycine max. L.Merrill) Crop Production by Using Biourine and Organic Mulch - Ana Amiroh; Achmad Anton Prastyo; Mahayu Woro Lestari; Palupi Puspitorini (Universitas Panji Sakti, 2021)
Soybean (Glycine max L.Merrill) is one of the main food commodities in Indonesia. The need for soybeans continues to increase in line with the increasing population of Indonesia. To overcome the problem of the gap between soybean production and consumption, efforts can be made to increase soybean production through fertilizers. Apart from fertilizers, mulching is an important component in efforts to increase plant growth and yield. Therefore, liquid organic fertilizer and organic mulch are the right innovations to be applied to support the growth and production of these soybean plants. The research method used was a randomized block design (RBD) with a factorial pattern with 3 replications, which consisted of 2 factors. The first factor was Liquid Organic Fertilizer (P) consisting of 3 levels, namely P1 (cow urine), P2 (goat urine), P3 (rabbit urine). The second factor was kinds of organic mulch with 3 levels, namely M0 (no mulch), M1 (straw mulch), M2 (husk mulch). The purpose of this study was to determine the effect of livestock bio urine and organic mulch on the growth and production of soybean (Glycine max. L,Merril). From the results of observations and calculations through analysis of variance, it can be concluded that the ones that give high production are the treatment of Rabbit Urine Liquid Organic Fertilizer and Organic Straw Mulch (P3M1).